2008
DOI: 10.1210/jc.2007-2055
|View full text |Cite
|
Sign up to set email alerts
|

Roles of Clinical Criteria, Computed Tomography Scan, and Adrenal Vein Sampling in Differential Diagnosis of Primary Aldosteronism Subtypes

Abstract: This study underlines the central role of AVS in the subtype diagnosis of PA. The use of the clinical criteria to distinguish between APA and BAH did not display a satisfactory diagnostic power.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
97
1
3

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
3
1

Relationship

3
6

Authors

Journals

citations
Cited by 152 publications
(104 citation statements)
references
References 19 publications
3
97
1
3
Order By: Relevance
“…3 Our study revealed that hypokalemia was seen in only 22.2 percent of cardiovascular diseases patients whereas the recent studies carried out by Mulatero et al and E. BornFrontsberg et al revealed that hypokalemia was seen in more than 50% of cardiovascular diseases. 4 Hypokalemia is associated with decrease in myocardial membrane permeability resulting in arrhythmia and sudden cardiac arrest which is similar to our results. 5 It has been reported that hypokalemia is independently associated with severity of arrhythmias in patients with acute myocardial infarction, and chronic hypokalemia is not associated with higher incidence of intra operative dysrhythmias.…”
Section: Discussionsupporting
confidence: 92%
“…3 Our study revealed that hypokalemia was seen in only 22.2 percent of cardiovascular diseases patients whereas the recent studies carried out by Mulatero et al and E. BornFrontsberg et al revealed that hypokalemia was seen in more than 50% of cardiovascular diseases. 4 Hypokalemia is associated with decrease in myocardial membrane permeability resulting in arrhythmia and sudden cardiac arrest which is similar to our results. 5 It has been reported that hypokalemia is independently associated with severity of arrhythmias in patients with acute myocardial infarction, and chronic hypokalemia is not associated with higher incidence of intra operative dysrhythmias.…”
Section: Discussionsupporting
confidence: 92%
“…However, it should be noted that, in our experience, patients with bilaterally normal appearance of the adrenal glands on computed tomography scanning are often associated with a very high probability of bilateral adrenal hyperplasia (95%). 20 A limitation of the present study is that the prevalence of FH-III has been based on the clinical phenotype. When the present article was in preparation, Choi et al 18 demonstrated the genetic cause determining FH-III as a mutation in the potassium channel KCNJ5.…”
Section: Discussionmentioning
confidence: 94%
“…20 Briefly, patients were screened using the serum aldosterone:plasma renin activity (PRA) ratio (ARR), and PA was confirmed using the intravenous saline load test. 21 All of the patients with confirmed PA underwent computed tomography scanning and AVS.…”
Section: Diagnosis Of Pamentioning
confidence: 99%
“…15 To date, proposed clinical prediction scores cannot replace AVS. [16][17][18][19][20] An interesting novel approach consists of the measurement of a selected steroid profile by mass spectrometry. 21,22 Nevertheless, additional diagnostic steps will be needed to localize potential APA.…”
Section: Hypertensionmentioning
confidence: 99%